2017
DOI: 10.1111/1462-2920.13837
|View full text |Cite
|
Sign up to set email alerts
|

The CpxR/CpxA system contributes to Salmonella gold‐resistance by controlling the GolS‐dependent gesABC transcription

Abstract: Several regulatory systems contribute to bacterial resistance to heavy metals controlling the expression of factors required to eliminate the intoxicant and/or to repair the damage caused by it. In Salmonella, the response to Au ions is mediated by the specific metalloregulator GolS that, among other genes, controls the expression of the RND-efflux pump GesABC. In this work, we demonstrate that CpxR/CpxA, a main cell-envelope stress-responding system, promotes gesABC transcription in the presence of Au ions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…This relationship was confirmed by cpxRA knockouts that demonstrated heightened gold sensitivity compared to the wild-type after Au exposure. These results support interaction between metal resistance and general stress response systems in bacteria (Cerminati et al 2017). In E. coli, it has been shown that CueR, the transcriptional regulator of the cue operon that activates the promoter of CopA, is triggered by gold salts through cysteine residues that can recognize gold, silver, and copper.…”
Section: Goldsupporting
confidence: 68%
“…This relationship was confirmed by cpxRA knockouts that demonstrated heightened gold sensitivity compared to the wild-type after Au exposure. These results support interaction between metal resistance and general stress response systems in bacteria (Cerminati et al 2017). In E. coli, it has been shown that CueR, the transcriptional regulator of the cue operon that activates the promoter of CopA, is triggered by gold salts through cysteine residues that can recognize gold, silver, and copper.…”
Section: Goldsupporting
confidence: 68%
“…We also showed that Cu induction of scsABCD depended on CpxR/CpxA (Fig. 1, 2, and 3), a two-component system essential for preserving and/or repairing periplasmic or inner membrane proteins damaged by different physical or chemical agents, including metals such as Cu, Zn, and Au (36,37,45). Our results indicate that, like scsA transcription, transcription of scsB, scsC, and scsD is driven by the CpxR-dependent scsA promoter, at least during copper stress.…”
Section: Discussionmentioning
confidence: 74%
“…Protein-DNA interaction assays. EMSAs and DNase I footprinting assays were performed using 6 fmol of a 32 P-labeled DNA fragment containing the scsABCD promoter and CpxR-P, basically as described previously (16,45). CpxR-P was obtained by incubating purified His-tagged CpxR with 25 mM acetyl phosphate for 1 h at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Prediction of CpxR-binding site. The consensus motif for the CpxR-binding site was generated by training the Multiple Expectation Maximization for motif Elicitation (MEME) tool (46) using as input cognate binding sequences in the promoter regions of the following CpxR-regulated genes from Salmonella: cpxP1, cpxP2, htrA, ppiA, yccA, spy, dsbA, amiA, amiC, cueP, gesA, and scsA (71)(72)(73)(74)(75). The obtained matrix was then submitted to the Find Individual Motif Occurrences (FIMO) tool to detect the presence of the motif in the promoter region of the prtA gene from S. marcescens (47).…”
Section: Methodsmentioning
confidence: 99%